Genetic relationships among okra (Abelmoschus esculentus (L.) Moench) cultivars in Nigeria - Bashir O. Bello; D. AMINU (Acta Agriculturae Slovenica)
This study was conducted on okra (Abelmoschus esculentus (L.) Moench) cultivars at the Teaching and Research Farm, University of Maiduguri, Nigeria. The objective was to evaluate the level of genetic divergence and heritability of eight characters in 2015 and 2016 dry seasons using irrigation. The results showed highly significant (p<0.01) differences in the ten okra cultivars for days to anthesis, plant height, fresh capsule length, fresh mass per capsule and fresh capsule diameter across the two years. A high genotypic coefficient of variation, heritability, and genetic advance were detected in all the characters except for days to anthesis and fresh capsule diameter. This implied that different genetic constitution and preponderance of additive effects governed these characters, thus presenting a significant opportunity for selection. The Mahanalobis D2 analysis allotted the ten cultivars into four clusters. The highest was cluster I comprising four cultivars, followed by cluster II containing three cultivars, cluster III consisting two cultivars, and cluster IV with mono genotypic. The three most superior okra cultivars (Salkade, Y’ar gagure and Kwadag) for yield and related characters could be exploited directly or introgressed with other promising ones in future breeding programs.